2017
DOI: 10.1097/lbr.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

A Single US Center Experience of Transbronchial Lung Cryobiopsy for Diagnosing Interstitial Lung Disease With a 2-Scope Technique

Abstract: Background:Transbronchial lung cryobiopsy (TBLC) has been used to establish the diagnosis of interstitial lung disease (ILD) in recent years. The technique and diagnostic yield vary among institutions. We report a new 2-scope technique and the results of TBLC in our institution.Methods:This is a retrospective chart review of patients who underwent TBLC for evaluation of ILD. Bronchoscopy with TBLC was performed by a board-certified interventional pulmonologist with a 2-scope technique under general anesthesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 14 publications
3
68
1
Order By: Relevance
“…In an in vivo animal study of large airway mucosal biopsy using both cryoprobes, mean biopsy diameter was only slightly larger using the 2.4 mm probe after 1, 2, and 3 second freeze times and biopsy weight was not significantly different after 3 second freezes (60); how well this reflects cryoprobe behavior in the peripheral lung is not clear. Neither probe size is predominant in published cases to date and some series report using both probes in an interchangeable fashion (5,44,45,47). Likewise, both carbon dioxide and nitrous oxide have seen wide use as the cryogen gas for cryobiopsy.…”
Section: Cryoprobe Size Cryogen and Activation-freeze Timementioning
confidence: 99%
See 1 more Smart Citation
“…In an in vivo animal study of large airway mucosal biopsy using both cryoprobes, mean biopsy diameter was only slightly larger using the 2.4 mm probe after 1, 2, and 3 second freeze times and biopsy weight was not significantly different after 3 second freezes (60); how well this reflects cryoprobe behavior in the peripheral lung is not clear. Neither probe size is predominant in published cases to date and some series report using both probes in an interchangeable fashion (5,44,45,47). Likewise, both carbon dioxide and nitrous oxide have seen wide use as the cryogen gas for cryobiopsy.…”
Section: Cryoprobe Size Cryogen and Activation-freeze Timementioning
confidence: 99%
“…The lower lobes are most commonly biopsied, with current studies evenly split between sampling a single segment or multiple segments. Biopsy of multiple lobes has been less commonly reported (29,30,35,37,(44)(45)(46)50,64) but is of potential interest given SLB data suggesting interlobar histopathological discordance is common (65).…”
Section: Biopsy Target Selection and Biopsy Numbermentioning
confidence: 99%
“…The acute exacerbation after SLB is hypothesized to be related to barotrauma during single lung ventilation and perhaps oxygen toxicity manifesting first in the lung not submitted to biopsy. The analysis of data already published on TBCB documents 7 deaths within a month after the procedure: 1 patient died from respiratory failure after TBCB due to lymphangitic carcinomatosis, 1 from acute myocardial infarction manifesting weeks later, 1 from pulmonary edema from newly diagnosed severe aortic stenosis, 1 with organizing pneumonia and who was on palliative care, 1 from pulmonary embolism, 2 patients from acute exacerbation of IPF [27,[40][41][42] from acute exacerbation, diffuse alveolar damage was the histological background and the complication developed after significant procedural complications such as tension pneumothorax and subsequent ventilation with high positive airway pressures or severe bleeding). A more recent case of acute exacerbation of ILD as a complication of TBCB has been reported in a patient with nonspecific interstitial pneumonitis (although this case report does not describe the TLCB technique specifically, analysis of histology, description of HRCT features, and clinical information documenting the presence of a stable disease or rapid progressive deterioration before the TBCB) [43].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, different procedural methods have been reported in different studies. Most commonly, the procedure has been performed with an artificial airway in place (endotracheal tube, laryngeal mask airway or a rigid bronchoscope) . Some studies have also reported, performing the procedure under conscious sedation, without an artificial airway .…”
Section: Introductionmentioning
confidence: 99%